Alternativas para melhorar o desenvolvimento e a criotolerância de embriões bovinos produzidos in vitro - Marques, Thaisa Campos (2016)
Melatonin treatment and blastocoel collapse had been suggested to be potent options to enhance embryo development and viability after cryopreservation of bovine embryos. The present study tested these alternatives with the aim to improve cryotolerance of bovine embryos produced in vitro. First, the effects of melatonin (MEL) were evaluated at three concentrations in Maturation Media (IVM) and/or Culture Media (IVC) (0, 10-7, 10-9, 10-11 M). The results showed that MEL10-9 in IVM could improve slightly the cleavage rate. However, when applied during IVC, MEL10-9 resulted in improved blastocysts rates and reduced numbers of apoptotic cells (NAC), a higher expression of antioxidative genes without changing the expression metabolism-related, placentation and anti-apoptotic genes. After, the MEL treatment giving the best result in first experiment (MEL 10-9 M in IVC) was combined with blastocoel collapse (BC) immediatly before vitrification. The survival and embryo quality were investigated. This experiment confirmed that independent of BC, MEL supplementation in IVC enhanced re-expansion and hatching rates of vitrified embryos. However, embryos cultured without MEL required more time during re-culture for all expansion. Embryos produced with MEL had similar NAC irrespective of vitrification and BC. BC did not affect embryo quality, in terms of the expression of genes involved in metabolism, oxidative stress, cell repair, placentation and implantation. Therefore, this research concluded that: (i) at 10-9 M concentration, MEL used during IVC improved embryo quality and development, and it minimized the oxidative stress and apoptosis in cells; (ii) embryos cultured with melatonin, vitrified and re-cultured can be transfered in less time; (iii) the blastocoel collapse benefited hatching when embryos were cultured with MEL in IVC; (iv) embryos cultured in IVC with MEL showed better quality and viability, and independently of BC. This information has a potential value for researchs on embryo cryotolerance.